Association between objectively measured static standing and low back pain – a cross-sectional study among blue-collar workers. Issue 9 (2nd September 2018) - Locks, Francisco; Gupta, Nidhi; Hallman, David; Birk Jørgensen, Marie; Oliveira, Ana Beatriz; Holtermann, Andreas
Abstract: This study aims to investigate the cross-sectional association between objectively measured total time and temporal patterns of static standing (short bouts: 0–5 min; moderate bouts: >5–10 min; and long bouts: >10 min) during work and leisure and low back pain (LBP) among 698 blue-collar workers. Workers reported LBP on a 0–10 scale. The association between time spent on static standing and LBP was tested with linear regression. A positive association with LBP intensity was found for long bouts of static standing ( β = 0.27) during total day (work + leisure), and total static standing time at leisure ( β = 0.12). No significant associations were found for static standing during work and LBP intensity. These findings indicate that particularly long bouts of static standing over the entire day contribute to LBP in blue-collar workers. Practitioner Summary: The association between LBP and static standing time was investigated. This study indicates that prolonged time standing during total day and standing during leisure are positively associated with LBP among blue-collar workers. Therefore, practitioners should consider long periods of standing as a potential risk factor for LBP.